A new species of Chrysilla Thorell, 1887 from China (Araneae: Salticidae) - Wang, Lu-Yu; Zhang, Zhi-Sheng (Zootaxa, 2012)
The jumping spider genus Chrysilla, established by Thorell (1887) based on the male of C. lauta Thorell, 1887, is insufficiently known. Presently, seven species are included, but none of them is known by both sexes: three of them only by males (C. deelemani Prószyński & Deeleman-Reinhold, 2010; C. doriai Thorell, 1890 and the type species) and the other four only by females (C. albens Dyal, 1935; C. delicata Thorell, 1892; C. kolosvaryi Caporiacco, 1947 and C. pilosa (Karsch, 1878)) (Platnick 2011). Only the type species and C. deelemani from the Southeast Asia seem to belong to Chrysilla. Three species (C. delicata, C. doriai and C. pilosa) need to be revised and the others (C. albens and C. kolosvaryi) are misplaced (Prószyński & Deeleman-Reinhold 2010; Prószyński 2011).